A New Species of Gonionchus (Nematoda: Xyalidae) from the Firth of Clyde, with a Redescription of Enoploides spiculohamatus Schulz (Nematoda: Enoplidae) - Benwell, M. P. (Cahiers de Biologie Marine, 1981)
Locality: Firth of Clyde; Cabinet:
NeMys doc_id: 7439